Poly(glycidyl methacrylate-co-ethylene dimethacrylate) Macroporous Polymer Particles for the Immobilization of b-Galactosidase from Aspergillus oryzae - Sun, Sufang; Dong, Lingyun; Xu, Xiaobing; Shen, Shigang (Asian Journal of Chemistry, 2010)
Macroporous polymer particles containing surface epoxy groups were synthesized using glycidyl methacrylate (GMA) as monomer, ethylene dimethacrylate (EDMA) as crosslinking agent and dodecyl alcohol and cyclohexanol as porogenic agents by suspension copolymerization for immobilization of b -galactosidase. The scanning electron microscopy (SEM) micrographs were also done to characterize their surface structure. Under the optimum conditions, b-galactosidase from Aspergillus oryzae was immobilized on the support obtained above. The basic property and the kinetic data of the immobilized enzyme were determined and satisfactory results were obtained in enzyme activity, activity yield, pH stability, thermal stability, operational stability and Michaelis constants Km. It is concluded that the ploy(GMA-co-EDMA) is suitable to immobilize b-galactosidase from Aspergillus oryzae.